2012
DOI: 10.1128/aem.00660-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Class 1 Integrons in Multiresistant Escherichia coli Isolates from Poultry Litter

Abstract: This study describes the prevalence of arrays of class 1 integron cassettes and Qnr determinants (A, B, and S) in 19 fluoroquinolone-resistant Escherichia coli isolates from chicken litter. qnrS and qnrA were the predominant genes in these fluoroquinoloneresistant isolates, and an uncommon array of aacA4-catB3-dfrA1 gene cassettes from a class1 integron was found. Additionally, aadA1 and dfrA1 gene cassettes, encoding resistance to streptomycin and trimethoprim, constituted the most common genes identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…Sedentary integrons are DNA elements found in the chromosomes of many species and were initially discovered due to their association with AMR (Mazel, 2006;Partridge et al, 2009). In contrast to sedentary integrons, mobile resistance integrons are often found in plasmids (Ponce-Rivas et al, 2012). The role of these elements in the acquisition and dissemination of ARGs is crucial, especially in Gram-negative bacteria (Ponce-Rivas et al, 2012), but they are also present in Gram-positive bacteria (Nandi et al, 2004).…”
Section: Integronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedentary integrons are DNA elements found in the chromosomes of many species and were initially discovered due to their association with AMR (Mazel, 2006;Partridge et al, 2009). In contrast to sedentary integrons, mobile resistance integrons are often found in plasmids (Ponce-Rivas et al, 2012). The role of these elements in the acquisition and dissemination of ARGs is crucial, especially in Gram-negative bacteria (Ponce-Rivas et al, 2012), but they are also present in Gram-positive bacteria (Nandi et al, 2004).…”
Section: Integronsmentioning
confidence: 99%
“…In contrast to sedentary integrons, mobile resistance integrons are often found in plasmids (Ponce-Rivas et al, 2012). The role of these elements in the acquisition and dissemination of ARGs is crucial, especially in Gram-negative bacteria (Ponce-Rivas et al, 2012), but they are also present in Gram-positive bacteria (Nandi et al, 2004). Integrons contain the gene encoding integrase (IntI), an enzyme that allows the incorporation of circular DNA segments by site-specific recombination (Cambray et al, 2010).…”
Section: Integronsmentioning
confidence: 99%
“…In one of the studies on multiresistant poultry E . coli isolates it was found that resistance determinants were harboured in class 1 integron [ 42 ]. Most common carriages were observed for aadA1 and dfrA1 gene cassettes, encoding resistance to streptomycin and trimethoprim, which were either located on mega-plasmids or on the chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…[6] By amplifying, for example, the variable region of class 1 integrons from community DNA and subsequent Southern blot hybridization, Binh et al [49] demonstrated that aadA gene cassettes were introduced via manure into agricultural soils. Ponce-Rivas et al [50] used PCR to evaluate the prevalence and origin of class 1 integrons and Qnr determinants in fluoroquinolone-resistant Escherichia coli isolates from poultry litter. They showed that resistance determinants within E. coli of poultry origin are genetically diverse and suggested the need for surveillance programs focused on the detection of genetic elements related to horizontal transfer genes.…”
Section: Pcr-based Approachesmentioning
confidence: 99%